Application of the Constructivism Model to Improve Vocabulary and Communication of Class III Students at SPF State Elementary School Number 104244 Jati Sari Lubuk Pakam, Deli Serdang District, School Year 2023-2024 - Atmaja, Indah Sulistia Wardana; Sutikno, Sutikno (International Journal of Educational Research Excellence (IJERE), 2024)
The purpose of this study is to (1) find out whether the application of Gagnon and Collay's constructivism model can increase the vocabulary of grade III students of UPT SPF State Elementary School Number 104244 Jati Sari Lubuk Pakam using newspaper media. (2) To find out there is an interaction between the application of Gagnon and Collay's constructivism model with vocabulary. (3). To find out whether the application of the constructivism model of Gagnon and Collay can improve public communication of grade III students of UPT SPF State Elementary School Number 104244 Jati Sari Lubuk Pakam by using newspaper media. (4) To find out there is an interaction between the application of Gagnon and Collay's constructivism model with public communication. The research design used in this study is quantitative research. The population in this study is the entire class III UPT SPF State Elementary School Number 104244 Jati Sari Lubuk Pakam. The data collection technique uses Test Essay and Observation techniques. The research found that the constructivism model of Gagnon and Collay could increase vocabulary in grade III students of UPT SPF SDN No 104244 Jati Sari using newspaper media. However, the null hypothesis (Ho) was accepted, meaning there was no interaction between the model and vocabulary. In public communication, the alternative hypothesis (Ha) was accepted, and the null hypothesis (Ho) was accepted, indicating no interaction between the model and public communication.